The role of socialisation in producing moral judgement - Siti Nuraisyah Dassian (2019)
Theories of morality regarding the formation of moral judgement has been a topic of discussion in the field of psychology, sociology and philosophy. The question of whether morals are socially formed, and the extent of the influence of social forces on morality, have long been an interdisciplinary discussion. Family, culture, and society have often been identified as prominent factors that contribute to form an individual’s socialisation. This essay will explore the relationship between society and morality, and the key role that socialisation plays in the formation of moral judgement. I will argue that socialisation affects our intuition and predisposed responses, can provide an explanation for changing attitudes across time, and causes different social groups to have different moral judgements. I will also explain how there is a lack of persuasive power in moral reasoning due to its ex-post facto role in moral judgement. There is often a gap between how people ought to be and how they are because people want to avoid cognitive and ethical dissonance and are susceptible to emotion.